Expression profiling of MADS-box gene family revealed its role in vegetative development and stem ripening in S. spontaneum - Mahpara Fatima (Nature Portfolio, 2020)
Abstract Sugarcane is the most important sugar and biofuel crop. MADS-box genes encode transcription factors that are involved in developmental control and signal transduction in plants. Systematic analyses of MADS-box genes have been reported in many plant species, but its identification and characterization were not possible until a reference genome of autotetraploid wild type sugarcane specie, Saccharum spontaneum is available recently. We identified 182 MADS-box sequences in the S. spontaneum genome, which were annotated into 63 genes, including 6 (9.5%) genes with four alleles, 21 (33.3%) with three, 29 (46%) with two, 7 (11.1%) with one allele. Paralogs (tandem duplication and disperse duplicated) were also identified and characterized. These MADS-box genes were divided into two groups; Type-I (21 Mα, 4 Mβ, 4 Mγ) and Type-II (32 MIKCc, 2 MIKC*) through phylogenetic analysis with orthologs in Arabidopsis and sorghum. Structural diversity and distribution of motifs were studied in detail. Chromosomal localizations revealed that S. spontaneum MADS-box genes were randomly distributed across eight homologous chromosome groups. The expression profiles of these MADS-box genes were analyzed in leaves, roots, stem sections and after hormones treatment. Important alleles based on promoter analysis and expression variations were dissected. qRT-PCR analysis was performed to verify the expression pattern of pivotal S. spontaneum MADS-box genes and suggested that flower timing genes (SOC1 and SVP) may regulate vegetative development.